Structure of immune dysfunctions in patients with chronic urogenital infections - V. A. Kramarskiy; V. S. Gorin; A. I. Budaev; Y. V. Trusov (Acta Biomedica Scientifica, 2018)
In recent years, the growth of urogenital infections, often transforming into chronic forms, is one of the most common causes of reproductive damage in women. The aim of the research was to study the structure of immune dysfunctions in patients with chronic urogenital infection. A one-stage observational study of 80 women of reproductive age with chronic urogenital infections was carried out. The control group consisted of 40 healthy women-donors. The main outcome of the study was the severity of the immunocomprometry of the female. The contents of different subpopulations of lymphocytes (CD3+, CD4+ and CD8+ T-lymphocytes, CD20+ B-), phagocytic activity of granulocytes and monocytes were determined, the migration index, the migration inhibition index, and the exponential function were calculated. The complex of immune dysfunctions established in such patients included a decrease in the number of T-cells and, primarily, CD4+ lymphocytes and their low mitogenic reactivity, an increase in the proportion of natural killer cells, a decrease in the number of actively phagocytic neutrophils and monocytes, the last hydrogen peroxide, an increase in the production of IgA and IgG. Typical were combinations of these violations. Conclusions: T-lymphocyte-monocyte immune deficitiency with the activation of the humoral link and the defectiveness of phagocytosis is a distinctive characteristic of chronic urogenital infection.